HUBUNGAN KEPADATAN HUNIAN, LUAS VENTILASI, JENIS LANTAI DAN KEBIASAAN MEROKOK DALAM RUMAH DENGAN KEJADIAN ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS LAMPAHAN TAHUN 2024 - Hermadita, Friya; Muzaffar; Zulfikar (Jurnal Ilmiah Cerebral Medika, 2025)
ABSTRACT Acute Respiratory Tract Infection (ARI) is the main cause of morbidity and mortality of infectious diseases in the world. The group most at risk is toddlers. The incidence of ARI is always the first in the 10 most common diseases in the Lamapahan Community Health Center, the percentage of toddlers with the highest number of ARI cases is in the Lampahan Community Health Center. The purpose of this study was to determine the relationship between family members' smoking habits, residential density, ventilation area, and floor type with the incidence of ARI in toddlers in the working area of the Lampahan Community Health Center in 2024. This type of research uses a quantitative approach with a cross-sectional study design. The study was conducted on July 15-25, 2024. The population in this study was 1889 mothers who had toddlers, the sample in this study was 95 mothers who had toddlers who were taken by random sampling. Data collection using questionnaires by interview and observation, data were analyzed univariately and bivariately with the chi-square statistical test. The results of the study showed that 51 (53.7%) toddlers had ARI, and 43 (45.3%) had family members who smoked in the house, 40 (42.1%) housing density did not meet the requirements, 54 (56.8%) ventilation area did not meet the requirements, and 35 (36.8%) types of floors did not meet the requirements. The results of the chi-square test showed that there was a relationship between smoking habits in the house (p-value 0.000), housing density (p-value 0.003), ventilation area (p-value 0.096), and floor type (p-value 0.445). smoking habits in the house and residential density, ventilation area, type of house floor are factors that influence the incidence of ARI. There is a relationship between smoking habits in the house and residential density with the incidence of ARI, there is no relationship between ventilation area habits and type of floor with the incidence of ARI. It is expected that health workers will increase socialization to provide education related to the environment that meets the requirements and the dangers of smoking in the house. Keywords : ISPA, Residential Density, Ventilation Area, Floor Type, Smoking